Amphetamine-Decreased Progesterone and Estradiol Release in Rat Granulosa Cells: The Regulatory Role of cAMP- and Ca(2+)-Mediated Signaling Pathways - Chen, Chung-Yu (Biomedicines, 2021)
The purpose of this study is to evaluate the amphetamine effects on progesterone and estradiol production in rat granulosa cells and the underlying cellular regulatory mechanisms. Freshly dispersed rat granulosa cells were cultured with various test drugs in the presence of amphetamine, and the estradiol/progesterone production and the cytosolic cAMP level were measured. Additionally, the cytosolic-free Ca(2+) concentrations ([Ca(2+)]i) were measured to examine the role of Ca(2+) influx in the presence of amphetamine. Amphetamine in vitro inhibited both basal and porcine follicle-stimulating hormone-stimulated estradiol/progesterone release, and amphetamine significantly decreased steroidogenic enzyme activities. Adding 8-Bromo-cAMP did not recover the inhibitory effects of amphetamine on progesterone and estradiol release. H89 significantly decreased progesterone and estradiol basal release but failed to enhance a further amphetamine inhibitory effect. Amphetamine was capable of further suppressing the release of estradiol release under the presence of nifedipine. Pretreatment with the amphetamine for 2 h decreased the basal [Ca(2+)]i and prostaglandin F2α-stimulated increase of [Ca(2+)]i. Amphetamine inhibits progesterone and estradiol secretion in rat granulosa cells through a mechanism involving decreased PKA-downstream steroidogenic enzyme activity and L-type Ca(2+) channels. Our current findings show that it is necessary to study the possibility of amphetamine perturbing reproduction in females.